Tribo-performance of 80%WC + 20%TIO2 HVOF thermal spray coating on SS-404. (2020) - Haque, Unzarul; Singh, Gurmeet; Singh Gill, Harjot; Sehgal, Satbir S.
Abstract: Erosion wear occurs when solid particles impact on a metal surface with high velocity. In this work, the erosion wear of SS-404 is analyzed by utilizing slurry erosion pot tester. The test has been carried out with coated (WC-TiO2 ) and uncoated stainless steel (SS-404). The impact of different parameters such as rotational speed, particle concentration, and the time period and particle size on erosion wear of SS 404 has been examined. While performing experiments four distinct speeds such as 700, 950, 1200 and 1450 rpm with a time duration of 45, 90, 135 and 180 min have been considered. To protect SS 404 material from erosion the process named High-velocity oxy-fuel (HVOF) spray has been applied. At the end of the experiment, the impact of the above-defined parameters on slurry erosion wear of pipeline material using the Taguchi mechanism has been conducted. Signal to Noise Ratio (SNR) of the proposed work based on the smaller are better properties with coated and without coated material has been examined. The signal to noise ratio examined with and without a coating of SS 404 varies from 37.19 dB to 47.75 dB, 37.18 to 47.74, 37.16 to 47.72, and 37.20 to 47.76. Particle size was identified as the most influencing parameter for erosion wear in SS 404.